Structural adhesives modified with thermally expandable particles - Banea, Mariana D. (2016)
In this study, the behaviour of two structural adhesives modified with thermally expandable particles (TEPs) was investigated as a preliminary study for further investigations on the potential of TEPs in adhesive joints. Tensile bulk tests were performed to get the tensile properties of the adhesives and TEPs-modified adhesives. In order to determine the expansion temperature of the particles while encapsulated in these particular adhesive systems, the variation of the volume of adhesive samples modified with different TEPs concentration as a function of temperature was measured. Further, the possibility of any chemical interactions between TEPs and adhesives matrix in the TEPs-modified specimens was verified by a Fourier transform infrared spectroscopy analysis. Finally, the fracture surfaces of the unmodified and TEPs-modified specimens, as well as the dispersion and the morphology of the particles, were examined by a scanning electron microscopy analysis. It was found that the stiffness of the TEPs-modified adhesives is not affected by incorporation of TEPs in the adhesives matrix, while the tensile yield strength decreased by increasing the wt% TEPs content. In applications of such particular materials (TEPs-modified adhesives), the temperature should be controlled to stay between 90°C and 120°C in order to obtain the highest expansion ratio. At a lower temperature, not all the particles will expand, and above, the TEPs will deteriorate and as a result the TEPs-modified adhesives will deteriorate.